Aging, Neuromuscular Decline, and the Change in Physiological and Behavioral Complexity of Upper-Limb Movement Dynamics - S. Morrison; K. M. Newell (Journal of Aging Research)
Aging is characterized by a general decline in physiological and behavioral function that has been widely interpreted within the context of the loss of complexity hypothesis. In this paper, we examine the relation between aging, neuromuscular function and physiological-behavioral complexity in the arm-hand effector system, specifically with reference to physiological tremor and isometric force production. Experimental findings reveal that the adaptive behavioral consequences of the aging-related functional decline in neurophysiological processes are less pronounced in simple motor tasks which provides support for the proposition that the motor output is influenced by both extrinsic (e.g., task related) and intrinsic (e.g., coordination, weakness) factors. Moreover, the aging-related change in complexity can be bidirectional (increase or decrease) according to the influence of task constraints on the adaptation required of the intrinsic properties of the effector system.